The Community-Based Child Health Integrated Program in Iran: A Mixed-Methods Process Evaluation - Barzegari, Maliheh; Fathollahi, Pourya; Afsharpour, Fatemeh; Foroumandi, Elaheh (International Journal of Child Health and Nutrition, 2022)
Objectives: The community-based Child Health Integrated Program (CHIP) was established to improve children’s health status in Iran. The current study was performed to understand how this program was implemented and experienced by the care providers and target group. Methods: A total number of 249 mothers who had children under 5 years (clients) and 70 caregivers (providers) were selected from 42 health care centers of Tabriz city to participate in the study. Quantitative and qualitative data were collected using two separated semi-structured interviews as well as self-developed questionnaires. The mixed-method process evaluation study was examined and reported the exposure and satisfaction status of the clients, and reach, delivery, fidelity rates, and contextual factors toward the CHIP. Results: Overall, low reach (11.2%), moderate-exposure (62.6%), and high satisfaction (80.1%) rates of the clients were reported to the program. The fidelity rate of the program tools was 42.9%, considered as an inadequate rate. Anthropometric measurement and vaccination of the children, as well as face-to-face training sessions for the mothers, were well delivered. However, some parts of the program including follow-up and group training sessions were delivered poorly. Conclusions: This process evaluation study demonstrated that the CHIP is a promising intervention for improving children’s health care. However, the barriers identified in this study warrant consideration in subsequent health care needs among children. Further research is required to identify ways to improve the implementation and delivery of this intervention. Practice Implications: There is a dire need to enter some audit and feedback strategies in the form of monthly tracking of process indicators to extent of implementation of intervention components.